Respect and Responsibility of Karate Students at BKC Dojo Maung - Muhamad Naufal Habibi Ardani; Tedi Supriyadi; Muhammad Nur Alif (Journal of Physical Education Health and Sport, 2026)
Education is the goal of developing students' character as part of the formation of social behavior. It not only focuses on intellectual development but also plays an important role in instilling moral values and social attitudes that are reflected in daily life. This study aims to understand how karate instruction shapes students' views about respect and responsibility. This study used a descriptive framework and a qualitative technique to explain events that occur during karate training sessions. Regular training sessions were attended by seven karate students. Paperwork related to training activities, student interviews, and training observers were used to collect data. Data reduction, data presentation, and conclusion formulation based on the study findings were used to analyze the data. The results indicate that students’ respect is reflected in their habit of performing salutation (rei) to coaches and fellow students, paying attention to the coach’s instructions, and maintaining proper attitudes and behavior during training. Meanwhile, responsibilities include maintaining training equipment, ensuring the safety of training partners, being disciplined in attending training sessions, and following dojo rules. These attitudes are developed via continuing training activities, the implementation of dojo rules, and the role modeling of coaches. Karate instruction therefore helps students develop both their martial arts skills and their character.